Multilayer Microcapsules: Ultrasound‐Triggered Delivery of Anticancer Therapeutics from MRI‐Visible Multilayer Microcapsules (Adv. Therap. 5/2018). Issue 5 (7th September 2018) - Alford, Aaron; Rich, Megan; Kozlovskaya, Veronika; Chen, Jun; Sherwood, Jennifer; Bolding, Mark; Warram, Jason; Bao, Yuping; Kharlampieva, Eugenia
Abstract : In article number1800051, Jason Warram, Yuping Bao, Eugenia Kharlampieva and co‐workers demonstrate ultrasound‐triggered drug release from MRI‐visible polymeric microcapsules. Iron oxide nanoparticles are attached to the microcapsules which provide imaging contrast rivaling commercial contrast agents at a fraction of the metal concentration. The encapsulated drug is selectively released through ultrasound irradiation with minimized off‐target uptake.